The Effect of Potassium Diformate as Feed Additive on Immune Performances of Nilem (Osteochilus hasselti Valenciennes, 1842) Under Infection of Aeromonas hydrophila - Ibnu Bangkit Bioshina Suryadi; Desty Nurul Ulfa; Ayi Yustiati; Rosidah Rosidah (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2020)
This research aims to determine the most effective dosage of potassium diformate additives in feed to increase the body resistance of nilem carp (Osteochilus hasselti). This research used Complete Random Design (CRD) experimental method with 4 treatments and 4 replications. The treatment used was the addition of potassium diformate on feed (0 %, 0.1 %, 0.3 % and 0.5 %). After 28 days of treatment, nilem fingerlings were challenged with Aeromonas hydrophila bacteria with a density of 108 cfu ml-1. Parameters observed were the number of leukocytes, erythrocytes, survival rate, clinical symptoms and water quality. The result showed that leukocytes and erythrocytes number were significantly different in each treatment. Meanwhile, leukocytes and erythrocytes number of nilem fingerlings in challenged test were increased and decreased due to the addition of potassium diformate and A. hydrophila infection. Clinical symptoms after challenged test were relatively similar such as haemorhagic, ulceration, exopthalmia, dropsy and abnormal swimming movements. Therefore, survival rate of nilem fingerlings with 0.3 % of potassiun diformate was the highest compared to other treatments, namely 81.67 %.